Effect of Patella Alta on the Native Anatomometricity of the Medial Patellofemoral Complex: A Cadaveric Study. Issue 7 (31st July 2020) - Huddleston, Hailey; Campbell, Kevin; Redondo, Michael; Espinoza, Alejandro; Chahla, Jorge; Cole, Brian; Farr, Jack; Yanke, Adam
Objectives: Patella alta has been identified as an important risk factor for lateral patellar instability and medial patellofemoral complex (MPFC) reconstruction failure. To our knowledge, no prior study has analyzed the anisometry of the MPFC in the setting of patella alta as this may play a role in the postoperative outcomes and could affect surgical technique. Methods: Eight (n=8) fresh frozen cadaveric knees were used in this study. No IRB approval was needed at our institution due to the use of cadaveric specimen. The MPFC was identified and dissected along with the patellar tendon, and quadriceps tendon. A custom-made jig was utilized to evaluate MPFC lengths from 0-90° of flexion. Length was measured at four possible reconstruction locations (midpoint patella [MP], MPFC osseous center [FC], superior medial pole of the patella [SM], and quadriceps tendon [Q]) along the extensor mechanism using a 3D robotic arm. These measurements were repeated at 0, 20, 40, 60 and 90° degrees of flexion. Degrees of increasing severity of patella alta at Caton-Deschamps index (CDI) ratios of 1.0, 1.2, 1.4, and 1.6, were then investigated. Results: CDI and attachment sites significantly affect changes in MPFC length from 0-90° of flexion (p < 0.0005). Proximal attachment points had more robust length changes than distal ones and increases in CDI enhanced these differences. Point Q at CDI 1 was similar to SM at 1.2 (p = 0.234), SM and FC at 1.4 (p = 0.89 and p = 0.073) and FC at 1.6 (p = 0.928). SM at CDI of 1 was similar to FC at 1.2 and 1.4 (p = 0.414 and p = 0.503) and MP at 1.6 (p = 0.473), while FC at CDI 1 was similar to the FC at 1.2 (p = 0.157) and MP at 1.4 and 1.6 (p = 0.068 and p = 0.519). Finally, the MP was similar at CDI 1.2 (p = 0.888) and 1.4 (p = 0.385) compared to at CDI of 1. At the quadriceps points, MPFC length and flexion degrees showed a moderate negative linear correlation at a CDI of 1 (r = -0.484, p = 0.002) and 1.6 (r = -0.692, p < 0.0005) (Fig 1). At the MP location at a CDI ratio of 1.6, significant differences were seen at 0° vs 90° (p = 0.027), 0° vs 60° (p = 0.044), 0° vs 40° (p = 0.016), and 0° vs 20° (p = 0.044), suggesting differing length change properties between the Q and MP attachment sites. Conclusions: Anisometry varies with location of the patellar attachment and with patellar height within the MPFC. The superior aspect of the MPFC demonstrated the most isometric behavior, increasing linearly with increasing flexion. The inferior aspect of the MPFC retains a relatively constant length at 20 to 90° of flexion. Increasing CDI amplified these results. These findings demonstrate that proximal based grafts loosen significantly before engaging in the trochlea and this effect is exaggerated in the setting of patella alta. Furthermore, this data suggests that soft tissue surgical reconstructions may be modified to correct for patella alta in place of performing distalization, which carries significant morbidity.